Numerical and Experimental Analysis of the Influence of Projectile Impact Angle on Armour Plate Protection Capability - Pacek, Dawid; Badurowicz, Przemysław (Defence Science Journal, 2024)
This research manuscript describes the process of degradation of an Armox 600 armour plate during the impact of a 5.56×45 mm SS109 projectile. The creation process of the numerical FEM model of the projectile is presented. The projectile impact angle is set between 15° and 90°, and this phenomenon is investigated via numerical and experimental approaches. The experiment is conducted under the same conditions as the numerical approach to validate the FEM model. The experiments are conducted using a high-speed camera. This research manuscript presents the influence of the projectile impact angle on the degradation of the armour plate and its protection capability for different angles. The results demonstrate the dependence of the transferred energy on the armour plate, speed of the particles after impact, and trace dimensions on the armour plate for different impact angles.